2018
DOI: 10.1007/978-3-319-91137-3_16
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Heart Failure Abolishes Circadian Rhythms in Resting and Chemoreflex Breathing

Abstract: Physiological systems often display 24hr rhythms that vary with the light/dark cycle. Disruption of circadian physiological rhythms have been linked to the progression of various cardiovascular diseases, and advances in the understanding of these rhythms have led to novel interventions and improved clinical outcomes. Although respiratory function has been known to vary between the light and dark periods, circadian rhythms in breathing have been understudied in clinical conditions. In the current study, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a study of 717 patients after MI, decreased cyclic variation amplitude was a predictor of mortality ( 58 ). Diurnal variations in respiration and arterial BP were abolished in HF with reduced ejection fraction (HFrEF) ( 59 ). Circadian oscillations in calcineurin-dependent activities in the left ventricle of normal mice showed that calcineurin-dependent transcript levels and nuclear occupancy of the nuclear factor of activated T-cells fluctuate over the course of a day, peaking in the morning when mice enter a period of rest ( 60 ).…”
Section: Disruption Of the Circadian Rhythm In Hfmentioning
confidence: 99%
“…In a study of 717 patients after MI, decreased cyclic variation amplitude was a predictor of mortality ( 58 ). Diurnal variations in respiration and arterial BP were abolished in HF with reduced ejection fraction (HFrEF) ( 59 ). Circadian oscillations in calcineurin-dependent activities in the left ventricle of normal mice showed that calcineurin-dependent transcript levels and nuclear occupancy of the nuclear factor of activated T-cells fluctuate over the course of a day, peaking in the morning when mice enter a period of rest ( 60 ).…”
Section: Disruption Of the Circadian Rhythm In Hfmentioning
confidence: 99%